Implementasi Model Meaningful Instructional Design (MID) Pada Materi Energi Terbarukan Untuk Meningkatkan Hasil Belajar Kognitif Siswa Kelas X SMA N 1 Reteh - Agustina, Nurmalasari; Azhar; Irawan, Dedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the cognitive learning outcomes of physics through the application of the Meaningful Instructional Design (MID) learning model to improve cognitive learning outcomes on renewable energy in grade X students of SMA Negeri 1 Reteh. This study used a quasi-experimental method with a Posttest Only Control Group Design. The sample in this study was grade X5 with 36 students, using conventional learning, and grade X6 with 35 students, using the MID learning model. The data in this study were analyzed descriptively and inferentially. Based on students' cognitive learning outcomes in class, the implementation of MID learning was categorized as quite good with an average score of 65.28, while the implementation of conventional learning was categorized as poor with an average score of 50. It can be concluded that physics learning with the application of the MID learning model can improve students' cognitive learning outcomes on renewable energy in grade X students of SMA Negeri 1 Reteh.